Superbase-catalyzed stereo- and regioselective glycosylation with 2‑nitroglycals : facile access to 2‑amino-2-deoxy‑O‑glycosides - Pal, Kumar Bhaskar (2020)
An eﬃcient superbase-catalyzed stereo- and regio-selective glycosylation of 2-nitroglycals with high functional group compatibility is reported. The ion pair generated from alcohol and a catalytic amount of P4-t-Bu was vital for the successful implementation of this stereoselective glycosylation under mild conditions, producing moderate to good yields. Under reported reaction conditions, 2-nitrogalactals produce α-stereoisomers exclusively, while 2-nitroglucal yielded more β-products. The notable diﬀerence between the outcomes was investigated by the density functional theory (DFT) study. In addition, we have synthesized the key intermediate of a mucin-type core-6 glycoconjugate, thus illustrating the synthetic potency of this method.